Implementasi Teknologi Augmented Reality Dalam Pembelajaran Tajwid Kelas 5 Pada Hukum Bacaan Mim Sukun Dan Tanwin Berbasis MDA Framework - Faisal Reza Pradhana; Triana Harmini; Hanifa Ramadhani Ayuningrum S (SMATIKA JURNAL : STIKI Informatika Jurnal, 2023)
Tajwid learning at SD Birrul Walidain Muhammadiyah Sragen currently relies in person or Direct interaction between educators and learners, using textbooks as the primary source of material. However, the results of observations revealed that there were weaknesses in the methods currently used, especially in learning the science of recitation, where from the results of the pretest carried out on students, 79.41% of them got a score below 50 (grade scale 1-100). This research aims to design a learning application for the rules of reading "MIM sukun" and "tanwin" using Augmented Reality technology based on Android. The application contains material taken from the Tajwid book "Anshorul Qur'an." The design of the learning media takes the form of an Augmented Reality-based game, utilizing the Mechanics, Dynamics, and Aesthetics (MDA) Framework, with the design process following phases of the Software Development Life Cycle (SDLC), often referred to as the waterfall method. The research has resulted in an application called "Mahwid," which provides explanations and examples of readings for each rule of "MIM sukun" and "tanwin" in three-dimensional format. The application is developed using Android-based Augmented Reality technology, with a minimum requirement of Android version 8.0. Application testing involves black box testing, indicating the smooth operation of the application, as well as acceptability and compatibility testing, demonstrating that the application functions well on Android devices with a version of 8.0 and above. Testing has also been conducted with content experts, achieving a result of 93%, media experts at 91%, and 34 users reporting a satisfaction rate of 94%. With the positive conclusion of these tests, the application is considered suitable and appropriate for use as a learning tool in memorizing the Tajwid of the Qur'an.